The professional composing projects as elements dynamizers of the process and development of the professional skills of the computer engineers - Roberto Barrera Jimenez; Juan Silvio Cabrera Albert; Ana Delia Barrera Jimenez; Máryuri García González (ADIDE Federación, 2013)
The Cuban Education Manner centers its attention in forming a professional in correspondence with the technological advances, capable of guiding their behavior in the exercise of the profession with initiative, flexibility and autonomy, in heterogeneous and diverse stages, starting from the integration of know-how, abilities and goods which are expressed in a professional efficient acting, ethically and socially commited. The present article centers its attention in approaching the dynamic role that grants to the professional composing projects in favor of the process of formation and development of abilities in the students of the engineering computer science career, proposal that is supported, essentially, by the relationships between the system of professional abilities of the career, the generalizing  abilities of every year and the courses that represent the different disciplines.